Enhancing adolescent competence strategies for classroom management - Miller, Darcy Elizabeth (West/Wadsworth, 1998)
This text provides educators with material to deal with today's increasingly violent middle schools and high schools. It takes an eclectic approach to classroom and behavior management, not just using one orientation or method. It presents a variety of research-based methods and strategies that have been proven to work in managing the behavior of these specific age groups.